Selected papers presented at the workshop on biological reference points. Rome, 20-21 Apr 2004 - Lembo, G. (Roma (Italia), 2006)
Sumario (En)
Ilus.; 76 ref.
Keywords: RECURSOS PESQUEROS; PESCA; ENCUESTAS; ESTUDIOS DE CASOS PRACTICOS; SOSTENIBILIDAD; BIOLOGIA PESQUERA; DESARROLLO PESQUERO